A Tribute to the legend of Professor C.R.Rao: the centenary volume - Chaudhuri, Arijit; Gupta, Sat N; Roychoudhury, Rajkumar (Singapore: Springer Nature, 2021)
This book includes speeches given during five seminar sessions held in honor of Prof. C. R. Rao, on his 100th year. This book also contains a few write-ups touching on the diverse aspects of this august personality. The chapters pay tribute to Prof. C. R. Rao, the Padma Vibhushan awardee, by discussing his life and contributions to the field of statistics. The book also includes a chapter by the Abel Prize winner Prof. S. R. Varadhan who happened to successfully complete his Ph.D. under the guidance of Prof. C. R. Rao.
Information and the accuracy attainable in the estimation of statistical parameters -- A Few thoughts on India's statistical system -- A Tribute to Prof. C. R. Rao -- The Polaron problem -- C.R.Rao: a life in statistics -- A Secure end-to-end verifiable e-voting system using zero-knowledge proof and Blockchain -- Glimpses from the life and work of Dr. C.R.Rao: a living legend in statistics -- My memorable interactions with Professor C.R.Rao -- Further non-subjective priors for wrapped cauchy distributions -- Aspects of inductive inference in statistics and machine learning -- "To the seers, our ancestors" -- A Tiny tribute to a towering statistician -- Our Dr. Rao -- A Tribute to Professor C.R.Rao -- His experiments with truth -- C.R.rao -- Professor C R Rao: homage to the towering personality of Indian Statistical Institute --
Includes bibliographical references
Keywords: C.R.Rao -- Tribute